Environmental stress due to the interaction of noise, humidity and heat - Ngah-Lian Lau (1983)
To evaluate the harmful effects of environmental stress on man, the effects of noise (75dbA, 85dbA), heat (24°C, 67% R.H.; 30.75°C, 85% R.H.) and combinations of noise and heat (75dbA, 24°C, 67% R.H.; 85dbA, 30.75°C, 85% R.H.) were studied in a group of twelve normal young adults (nine women and three men). [Continues.]